Designing Image Processing-Based Banknote Identification Device for Blind People - Hartanto, Agung Dwi; Isnomo, Yoyok Heru Prasetyo; Purwandi , Ahmad Wahyu (Jurnal Jaringan Telekomunikasi, 2024)
Money is a tool used all over the world to make buying and selling transactions and must reach an agreement to complete the transaction. It is certain that everyone needs money as a daily necessity, even for people with disabilities such as the blind. The limitations of blind people are problems in vision and relying on hearing for communication. The method used is a camera that detects the images contained in banknotes and sends data to the Raspberry Pi as the main controller in the system. The Raspberry Pi will process the received data signal and produce output in the form of sound. Tests carried out by calculating the success of the tool in detecting each currency. And from testing the data, it was found that the success of reading the system is almost 100% in all tests that users can use to identify banknotes.